Sustainable finance and green economic growth: Evidence from the Indonesian banking sector - Zulbetti, Rita; Muzaffirah, Adzirah; Alfiana, Alfiana; Perwito, Perwito (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2025)
Green economic growth has emerged as a global priority in pursuing sustainable development. This study examines the role of resource allocation efficiency in supporting green economic growth, as influenced by green financing practices, sustainable finance policies, and green financial products. A quantitative research approach was employed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The study population consisted of 107 financial institutions. A purposive sampling technique was used to select 168 respondents from 84 banks, comprising senior managers, division heads, and executives responsible for implementing sustainable finance policies—averaging two respondents per institution. The results reveal that green financing practices, sustainable finance policies, and green financial products directly and significantly impact green economic growth. Moreover, resource allocation efficiency plays a mediating role in strengthening these relationships. These findings underscore the importance of the banking sector in driving innovation in green financial products, implementing sustainable finance policies, and enhancing resource utilization efficiency. In conclusion, the banking sector holds a strategic position in advancing green economic growth. Future research could extend this framework by examining the role of non-financial sectors or exploring how digital technology transformation facilitates green financing to support sustainable development goals further.